Cyberbullying di Twitter sebagai Risiko Sistemik: Analisis Desain Platform Berbasis Teori Masyarakat Risiko Ulrich Beck - Agustin, Nanda Riski; Ajizah, Tary Hadisti; Yunita Maharani; Sununianti, Vieronica Varbi; Istiqomah Istiqomah; Kurniawan, Deni Aries (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
The rapid development of social media, particularly Twitter, has given rise to a new form of social violence known as cyberbullying. This study aims to explore the phenomenon of cyberbullying on Twitter using Ulrich Beck's Risk Society Theory as an analytical framework. The research approach used is a literature review. This study perceives cyberbullying on Twitter as a modern, systemic risk, shaped by anonymity, cancel culture, and the individualization of risk. It acknowledges that Twitter's structural features, such as pseudonymous accounts and the rapid dissemination of information, exacerbate the potential for cyberbullying, while simultaneously positioning individual users as both victims and potential perpetrators of digital violence. These findings reinforce Beck's thesis that risks in advanced modernity are self-produced, institutionally distributed, and difficult to regulate, clearly reflected in the uncontrolled spread of cyberbullying in digital public spaces.